Surviving the Antarctic Winter—Life Stage Cold Tolerance and Ice Entrapment Survival in The Invasive Chironomid Midge Eretmoptera murphyi - Bartlett, Jesamine C; Convey, Peter; Hayward, Scott A L (Insects, 2020)
Keywords: Antarktis; fjærmygg; insektfysiologi; invasjonsbiologi; kuldeeksponering; kuldetoleranse; mikroklima; overvintring; termiske terskler; zoologi

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Sydpolfarerne Per Savio og Ole Must : liv i grenseland - Sandholm, Unni Aas (Temahefter Aas Sandholm, 2013)
Keywords: Antarktis; Southern Cross; Sydpolen; ekspedisjonen; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Antarctic pioneers : the voyage of the Belgica 1879-99 - Kløver, Geir O (Red.) (The Fram Museum, 2010)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Belgicaekspedisjonen 1897-1899 : den første overvintring i Antarktis - Amundsen, Roald; Kløver, Geir O. (Red.) (Frammuseet, 2009)
Publication Title: Roald Amundsens dagbøker
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Edition: 2005/08/01 Publisher: Cambridge University Press
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Supplement: S
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Johan Koren : feltzoolog og polar-pioner - Wikan, Steinar (Schibsted, 2000)
EN NORSK FELTZOOLOG OG POLAR-PIONER 17 år gammel drar snekkerlærlingen JOHAN KOREN ut fra hjembyen i Fredrikstad i 1897 som deltager i historiens første overvintringekspedisjon i Antarktis, Belgica-ekspedisjonen. Styrmann om bord er en landsmann, den unge Roald Amundsen. I likhet med ham, blir Koren snart kjent og omtalt som en av tidenes dristigste oppdagelsesreisende, med Antarktis og Arktis som virkefelt. Men for Koren blir berømmelsen ikke varig. Bare 39 år gammel dør han i spanskesyken, alene på et hospital i Vladivostok. Og med tiden går det slik at han blir "Gutten Norge glemte" - slik tittelen lød på en senere guttebok, inspirert av hans begivenhetsrike og dramatiske liv. Blant feltzoologer regnes han imidlertid den dag i dag som en pionerskikkelse, og rundt om i verdens zoologiske museer finnes tusenvis av vitnesbyrd om hans innsats for vitenskapen som samler av fugle- og dyrearter. Forfatteren, historikeren og biologen STEINAR WIKAN bygger denne beretningen på Johan Korens delvis bevarte dagbøker, samtlige brev, dokumenter og presseomtaler, erindringsbøker og - ikke minst - samtaler med en gammel mann i det fjerneste Sibir som kjente Koren.
Keywords: Antarktis; Belgica ekspedisjon; biografier; forskning; oppdagelser; overvintring; polarekspedisjoner; zoologi

Roald Amundsen's Belgica diary : the first scientific expedition to the Antarctic - Amundsen, Roald; Decleir, Hugo (Red.) (Bluntisham Books, 1999)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Dagboken fra Belgica-ekspedisjonen 1897-99 : Roald Amundsens første ferd til Antarktis - Amundsen, Roald (Vågemot miniforl., 1998)
Publication Title: Sydpol-serien
Keywords: Antarktis; Belgica (skip); Roald Amundsen; dagbøker; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Journal over den Belgiske Sydhavs-Expedition 97-99 - Koren, Johan (1988)
Pages: [60 s.]
Keywords: Antarktis; Belgica (skip); dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner

Belgica : den første overvintringen i Antarktis 1897-1899 - [Smedvig, Nora] ([Nordsjøselskapet], 1988)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; forskning; oppdagelsesreiser; overvintring; polarekspedisjoner; utstillinger

First on the Antarctic Continent: being an account of the British Antarctic Expedition 1898-1900 - Borchgrevink, Carsten Egeberg (C. Hurst & Company; Australian National University Press, 1980)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

The Last of "The Ten". Antarctic Pioneer Still Lives On (Antarctic, 1970)
Publisher: New Zealand Antarctic Society Place: Christchurch
Keywords: Antarktis; Hugh Blackwall Evans; Southern Cross; biografi; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

The first settlers - Quartermain, L B (South to the Pole : the early history of the Ross Sea sector, Antarctica, 1967)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; biologi; ekspedisjonen; geologi; meteorologi; overvintring; polarekspedisjoner

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

U južnogo poljusa god 1900 - Borchgrevink, Carsten Egeberg (1958)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Asahi Shimbun Sha, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Chatto & Windus, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

Maudheim : to år i Antarktis : den norsk-britisk-svenske vitenskapelige ekspedisjon til Antarktis 1949-1952 - Giæver, John (Gyldendal, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

Marking Time; Winter in the Antarctic; The Southern Cross story; The achievement of Roald Amundsen; The conquest of Antarctica by air - Nichol, J R (Stepping stones to the South Pole, 1948)
Keywords: Antarctic (skip); Antarktis; Carsten Borchgrevink; Henrik Johan Bull; Hjalmar Riiser; Kapp Adare; Larsen; Norvegia ekspedisjonene; Roald Amundsen; Southern Cross (skip); Sydpolsekspedisjonen; kartlegging; overvintring

Pojken som glömdes av sitt land - Evjenth, Håkon; Lundbergh, Arvid (Fahlcrantz & Gumælius, 1939)
Keywords: Antarktis; Belgica ekspedisjon; Johan Koren; biografier; overvintring

Gutten som Norge glemte : boken om Johan Koren - Evjenth, Håkon (Gyldendal, 1938)
Keywords: Antarktis; Belgica ekspedisjon; biografier; overvintring

Private expeditions - Borchgrevink - Gerlache - Nordenskioeld - Bruce - Drygalksi - Charcot - Filchner; Amundsen`s journey to the south pole - Markham, Clements R (The Lands of Silence : A History of Arctic and Antarctic Exploration, 1921)
Keywords: Antarktis; Carsten Borchgrevink; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; overvintring

Das Festland am Sydpol : die Expedititon zum Sydpolarland in den Jahren 1898-1900 - Borchgrevink, Carsten Egeberg (Schottlaender, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Nærmest Sydpolen : Aaret 1900 - Borchgrevink, Carsten Egeberg (Gyldendal, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Steam whalers; First Antarctic night - Mill, Hugh Robert (The siege of the south pole : the story of antarctic exploration, 1905)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Henrik Johan Bull; Kapp Adare; oppdagelsesreiser; overvintring; polareksspedisjoner; vitenskap

Extracts from the Private Diary of the Late Nicolai Hanson - Hanson, Nicolai (Report on the collections of natural history made in the Antarctic regions during the voyage of the "Southern Cross", 1902)
Keywords: Antarktis; Kapp Adare; Rosshavet; Southern Cross; ekspedisjonen; ekspedisjoner; fauna; flora; fugler; oppdagelsesreiser; overvintring; seler; zoologi

To the South Polar regions : expedition of 1898-1900 - Bernacchi, Louis Charles (Bluntisham Books, 1901)
Keywords: Antarktis; Southern Cross; astronomi; biografi; ekspedisjonen; ekspedisjoner; forskning; fysikk; geologi; klimatologi; oppdagelsesreiser; overvintring; zoologi

The "Southern Cross" Expedition to the Antarctic, 1899-1900 - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1900)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Southern Cross; biologi; ekspedisjonen; ekspedisjoner; forskning; geografi; meteorologi; oppdagelsesreiser; overvintring; zoologi

The "Southern Cross" Antarctic expedition - Newnes, George (The Strand Magazine, 1899)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; første landgang; oppdagelsesreiser; overvintring

Antarctic exploration - Borchgrevink, Carsten Egeberg (Strand Magazine, 1897)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; geografi; oppdagelsesreiser; overvintring

Den sidste antarctiske reise og foreløbig plan for en ny expedition. Foredrag den 30te oktober 1895 - Borchgrevink, Carsten Egeberg; Bull, Henrik Johan (Det Norske geografiske selskabs aarbok, 1896)
Publisher: Haffner & Hille Place: Kristiania
Keywords: Antarktis; Kapp Adare; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner

Is Antarctic exploration possible? (The Spectator, 1895)
Publisher: The Spectator
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; oppdagelsesreiser; overvintring